VD_FINDINFO Jug / 2016 / 110 vom 15. Oktober 2015 - VD Tribunal cantonal (2015)
PRÉSOMPTION D'INNOCENCE, ESCROQUERIE, CHANTAGE, MENACEDROIT PÉNAL | 146 al. 1 CP, 156 ch. 1 CP, 180 al. 1 CP, 10 CPP (CH)